Anatomical Responses of Bambusa blumeana Schult.f. Treated with Alpha-Naphthalene Acetic Acid - Saddoy, John Karlo Cruz; Tinio, Crusty Estoque; Aboc, Vinjoe Magalang; Luna, Amelita Carpio; Combalicer, Marilyn Sabalvaro; Maldia, Lerma San Jose (Jurnal Sylva Lestari, 2024)
The underlying mechanism of bamboo anatomical responses remains poorly understood when subjected to different levels of Alpha-Naphthalene Acetic Acid (Alpha-NAA) under nursery conditions. In this paper, we aim to examine the leaf and root anatomy of the Bambusa blumeana Schult.f., a potential bioremediation alternative species, treated with 0 ppm, 100 ppm, and 200 ppm of Alpha-NAA. The experimentation was executed in a completely randomized design within a 3-month experimentation period. Freehand sectioning was performed to collect the leaf and root transverse sections, and the photomicrographs were taken and analyzed. The results revealed that 200 ppm Alpha-NAA significantly increased the diameters of leaf fusoid cells and xylem. In the roots, the thickness of the rhizodermis, sclerenchymatous layer, cortex, and pericycle, as well as the diameter of the phloem, metaxylem, and pith, were significantly affected by the treatments. Generally, there is a weak to moderate correlation between the leaf and root anatomical structures based on Pearson’s correlation and a weak to strong correlation within the organ-specific anatomical structure. Thus, our findings elucidate the potential role of exogenous auxin in inducing anatomical changes that assist the growth and propagation of B. blumeana. Keywords: alpha-naphthalene acetic acid, bamboo, freehand sectioning, leaf anatomy, root anatomy